2008
DOI: 10.1126/science.1155164
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Uses Macropinocytosis and Apoptotic Mimicry to Enter Host Cells

Abstract: Viruses employ many different strategies to enter host cells. Vaccinia virus, a prototype poxvirus, enters cells in a pH-dependent fashion. Live cell imaging showed that fluorescent virus particles associated with and moved along filopodia to the cell body, where they were internalized after inducing the extrusion of large transient membrane blebs. p21-activated kinase 1 (PAK1) was activated by the virus, and the endocytic process had the general characteristics of macropinocytosis. The induction of blebs, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
791
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 713 publications
(823 citation statements)
references
References 25 publications
27
791
2
3
Order By: Relevance
“…Consistent with this, when release of cores into the cytosol was observed, it occurred from LAMP1‐containing vacuoles. We have previously shown that virus‐containing vacuoles positive for the endosomal content marker dextran do not contain transferrin at any time 34, 35 confirming that they are distinct from classical endosomes.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Consistent with this, when release of cores into the cytosol was observed, it occurred from LAMP1‐containing vacuoles. We have previously shown that virus‐containing vacuoles positive for the endosomal content marker dextran do not contain transferrin at any time 34, 35 confirming that they are distinct from classical endosomes.…”
Section: Resultsmentioning
confidence: 82%
“…We have previously employed this strategy to test the specificity of entry inhibitors 34, 55. To determine whether YM201636 inhibited MV entry, WR E EGFP MVs were bound to cells in the presence or absence of YM201636 and subsequently treated with pH 5.0 media (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations